2018
DOI: 10.1016/j.joca.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Femoral osteochondroplasty can be performed effectively without the risk of avascular necrosis or femoral neck fractures in an experimental ovine FAI model

Abstract: Femoral osteochondroplasty can be performed effectively and without the risk of AVN or femoral neck fractures in this ovine FAI model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Hip arthroscopy for cam-type resection is increasingly performed without a complete understanding of the causes of the development of the cam deformity. An experimental ovine FAI model to simulate cam resection has been proposed recently and may help in understanding the development of the cam deformity using advanced MR techniques [34]. At an average 12-year followup after prophylactic pinning, the HHS and the HOOS assessing hip pain and function were good (Table 3) in all patients who did not undergo further FAI surgery, although it is important to remember that four patients did undergo this additional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroscopy for cam-type resection is increasingly performed without a complete understanding of the causes of the development of the cam deformity. An experimental ovine FAI model to simulate cam resection has been proposed recently and may help in understanding the development of the cam deformity using advanced MR techniques [34]. At an average 12-year followup after prophylactic pinning, the HHS and the HOOS assessing hip pain and function were good (Table 3) in all patients who did not undergo further FAI surgery, although it is important to remember that four patients did undergo this additional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the spatial orientation of the pelvis in sheep, this should occur in the superior acetabulum and not posteroinferiorly as observed in our study. Similarly, an interruption of the femoral head blood supply after intertrochanteric osteotomy is unlikely, since it could be shown that the experimental FAI induction in sheep can be performed safely without the risk of avascular necrosis 29 . We interpret these results as proof that the peripheral chondral damage in the ovine FAI model is caused by inclusion type FAI with an opposed central contre-coup mechanism in hip extension.…”
Section: Table Imentioning
confidence: 99%
“…The surgical procedure and anesthesia were performed according to the institutional routine protocol for surgery in sheep [33,36]. Anesthesia was induced through a jugular catheter and via an intravenous, constant-rate infusion of propofol plus a maximum 5% isoflurane (Minrad Inc, Buffalo, NY, USA) inhalation.…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…Using the same incision, we performed an intermuscular, anterior approach (interval between the gluteus medius and the minimus muscle) for exposure of the joint capsule. After an H-shaped capsulotomy, we performed the femoral osteochondroplasty with curved chisels and a high-speed burr (Air Pen Drive; DePuy Synthes) until impingement-free ROM was established [33]. This approach reportedly prevents laceration of the retinacular vessels, which ensure the vascular supply to the femoral head [33,40].…”
Section: Description Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation